Treatment of vinasse by adsorption on activated carbon from sugarcane bagasse agglomerated with Al2O3 - Nippes, Ramiro Picoli; Macruz, Paula Derksen; Fernandes, Nádia Regina Camargo; Gimenes, Marcelino Luiz (Acta Scientiarum. Technology, 2022)
The objective of this work was to produce and characterize activated carbon from sugarcane bagasse agglomerated with Alumina (Al2O3) and apply it in treatment of vinasse pretreated by coagulation-flocculation to reduce the toxics parameters of vinasse. The adsorbent was characterized from textural analysis, XRD, pHZPC, SEM and EDS. Adsorption isotherms, adsorption kinetics and thermodynamic parameters of the process were obtained. The Langmuir isotherm model fitted the experimental data better and the pseudo-first-order model best represented the adsorption kinetics. The process was spontaneous, exothermic and with increased entropy. The combined coagulation-flocculation/adsorption process was efficient in reducing the parameters of color, turbidity, COD, TOC and toxicity of the vinasse with removal rates of 73.50, 96.06, 72.65, 76.08, 78% respectively.